PEMURNIAN DAN KARAKTERISASI POLIFENOLOKSIDASE BUAH ADVOKAT (PERSEA GRATISSIMA, GAERTN.) - Purwanto
Up to the present the prevention of enzymic browning in avocado fruits has not been successfully carried out. The presence of several kind of polyphenoloxidase (FPO) in avocado which are responsible for the browning have not yet been fully characterized hitherto and this makes the prevention of browning difficult. The purpose of this research is to purify and characterize the avocado FPO, which was isolate1 from the supernatant of a 90% saturated ammonium sulphate fraction. No previous work has been reported so far on the presence of PPO in this supernatant. In this research work, the supernatant fraction was concentrated by lyophilization, followed by gel filtration through Sephadex GÂ—75 column. The elution pattern revealed 1 peak which appeared to be PPO with a specific activity of ca 10.9. The purity was ca 68 times if compared with the crude extract or 4 times if compared with the supernatant fraction. Purity test using the polyacrylamide disc gel technique revealed that the obtained single peak as mentioned above only consisted of 1 protein band which after it had been examined appeared to be PPO. It needs to be mentioned here that the crude enzyme extract was resolved by polyacrylamide disc gel electrophoresis into 6 protein patterns, and 3 of which were PPO. In the supernatant fraction however, 5 protein patterns were observed and 3 of which were PPO. The substrate specificity of PPO was tested on various substances among others phenol, resorcinol, orcinol, phloroglucinol, pyrogallol and gallic acid. Only pyrogallol was catalyzed positively, while gallic acid was to a lesser degree catalyzed. Hence it is suggested that the isolated PPO is a pyrogallolase. The investigation of this pyrogallolase activity was carried out at pH 6.5 which incubation at 30Â°C for 30 minutes. The reaction was terminated by adding trichloroacetic acid solution. The activity of the enzyme was measured by a colorimetrical determination at 410 nm of the product of the reaction. The pyrogallolase appeared to be thermolabile. Kinetic studies showed that the Km was 0.80 x 10-3 M. The optimum pH activity of this enzyme was found to be 7.6. Further investigation on inhibitors showed that ascorbic acid (0.50 x 10-4 M), NaHSO3 (1.52 x 10-4 M), K2S205 (3.20 x 10-4 M) and L-cysteine hydrochloric acid (6.06 x 10-4M) inhibited the pyrogallolase activity totally. For malic acid and citric acid, sufficient higher concentrations were needed, i.e. (37.29 x 10-4 M) and (47.29 x 10-4 M) respectively. Further experiments revealed that thiourea (12.10 x 10-4 M) and sodium diethyldithiocarbamate (11.32 x 10-4 M) were also able to inhibit pyrogallolase for ca 38% and 73%, respectively. It can be concluded that the pyrogallolase investigated in this research is of a new kind not yet previously studied.